Transverse shear stress within surface layer and its effects. (February 2020) - Yan, Ge; Huang, Zaixing
When the transverse shear stress within a surface layer is taken into account, what happens in the deformation of micro- or nanoscale solids? The relevant problems are investigated by analyzing the deformation of a micro- or nanosized solid ellipsoid. The results show that both the stress and the deformation of a micro- or nanosized ellipsoid increase after the transverse shear stress within the surface layer is introduced, and that the maximal stress always occurs at both ends of the long axis of the ellipsoid. Unlike the prediction given by the Gurtin–Murdoch model, the calculation coming from the model of this paper predicts that the micro- or nanosized ellipsoid subjected to hydrostatic pressure contracts radially in the middle section and expands radially on both sides of the middle section. This difference provides an experimental standard to verify two models.